Special Economic Zones: in Countries Neighbouring India and Beyond - Mittal, Vinati Bhargava (2007)
In this era of global competition, a large number of governments from the developing as well as the developed world are dismantling rigid barriers to trade and commerce, and reformulating laws, rules and regulations to encourage foreign investors to make investment on their shores in a bid to boost their economies, attract foreign exchange, encourage exports, aid in the transfer of technical know-how, and generate employment. For this purpose, several countries have demarcated areas as zones that offer investors state-of-art technology as well as infrastructure, income tax incentives, exemption from heavy custom duties, liberal labour laws, storage capacities and other facilities.